A comparison of reactor configuration using a fruit waste fed two-stage anaerobic up-flow leachate reactor microbial fuel cell and a single-stage microbial fuel cell. (April 2023) - Zafar, Hirra; Peleato, Nicolas; Roberts, Deborah
Graphical abstract: Highlights: MFC configurations were compared in terms of substrate removal and power generation. A maximum power density of 221 mW/m 2 and 218 mW/m 2 was observed. Two-stage MFC removed 118% higher CODs compared to single-stage MFC. Decline in voltage is positively correlated with COD concentration level. Coulombic efficiency of AULRMFC was 86.7% lower than single-chamber MFC. Abstract: Food waste generation and its consequent environmental impacts are increasing due to rapid urbanization, the global population, and associated food demand. Microbial fuel cells (MFCs) are a sustainable technology through which this food waste can be treated and used to produce bioelectricity. This study used two MFC configurations, a two-stage anaerobic up-flow leachate reactor MFC and a single-stage MFC, comparing the potential to treat solid fruit waste and fruit waste leachate. The two-stage MFC showed a higher potential to remove substrate at a shorter time compared to single-stage MFC. In 30 days, the two-stage anaerobic up-flow leachate reactor had a power density of 221 mW/m 2 . It was able to remove more total solids (by 95 %), volatile solids (by 70 %), total chemical oxygen demand (by 83 %), soluble chemical oxygen demand (by 87 %), and carbohydrates (by 33 %) compared to the single-stage MFC. However, the single-stage MFC showed higher coulombic efficiency (by 86.7 %) compared to the two-stage MFC. The efficiency of single-stage MFC improved by adding buffer and maintaining a neutral pH level of the substrate. The results of this study emphasize the importance of reactor design and demonstrate that MFC can be a viable technology to generate bioenergy from food waste.